Resyllabification of English Loanwords Borrowed from Indonesian Language - Adria Indah Putranti (Universitas Sanata Dharma, 2014)
Resyllabification happens when the syllable structure of the source language differ from that of the recipient language. This article aims at observing how Indonesian words borrowed by English language are resyllabified in order to match with the syllable structures of English language as the recipient language. Results show that the resyllabification of English loanwords can be analyzed by applying deletion and addition rule. The result of deletion rule is the reduced number of syllable of loanwords (such as in cutch, cockatoo, cajeput, kris, prau, tombac, and trepan), while addition rule results on the addition of the number of syllable (such as in catechu, caladium, mangosteen, and pandanus). Keywords: resyllabification, borrowing, source language, recipient language